User Engagement with the AICCRA-KMD Mobile App and web Dashboard - Akshatha, Annaiah (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
The AICCRA-KMD mobile application developed collaboratively by the International Livestock Research Institute (ILRI) and KMD under the AICCRA project in 2023. The KMD mobile App is an innovative, Android-based tool designed to enhance field data collection and agro-advisory services. This app empowers stakeholders to gather agro-meteorological data while providing weather and climate information from platform like KAOP. Moreover, designed as a user-friendly platform, the app serves to collect vital agro-meteorological and rainfall data directly from the field, leveraging manual rain gauges installed in farmers' fields across Kenya. The AICCRA-KMD mobile app is specifically tailored to support County Directors of Meteorological Services (CDMs), Ward Agricultural Extension staff (WAES), member of Cereal growers’ association (CGA) and selected volunteer observer farmers (Enumerators) across the eight KCEP-CRAL Counties to gather daily rainfall and weekly crop information. CDMs utilize the AICCRA-KMD app to register rain gauge locations, while selected farmers (enumerators) are responsible for recording daily rainfall and capturing weekly key crop-related information, such as Crop types and varieties, Pest infestations, Disease prevalence, Weather-related hazards, Crop yields. The app is operational in eight KCEP-CRAL counties -Embu, Kilifi, Kitui, Kwale, Makueni, Machakos, Taita Taveta, and Tharaka-Nithi. It allows real-time data upload, ensuring seamless integration with a web-based dashboard for data visualization and analysis. This system minimizes errors in data collection, streamlines analysis, and facilitates informed decision-making for climate resilience and adaptation. The app is available on the Google Play Store, ensuring easy access for registered users. Its secure login system ensures data integrity and user accountability, fostering a reliable and efficient data ecosystem. By leveraging the AICCRA-KMD Mobile App, stakeholders can make data-driven decisions, enabling Kenya's smallholder farmers to better adapt to climate variability and build resilience. The app reflects a significant step forward in integrating technological advancements into agricultural practices for sustainable development.